Investigation of the contents of three main bio-active substances in the seed oil of the neem trees planted in Ninh Thuan province, Vietnam. - Do, Vu Van; Thang, Nguyen Tien; Suong, Ngo Ke (Academia Journal of Biology, 2014)
By the cold pressing method of the neem (Azadirachta indica A. Juss) seed kernels at 40oC, we have received 32.6% neem oil and 67.4% neem cake. The results of the analysis on high performance liquid chromatography (HPLC) and gas chromatography (GC) showed that there were three main bio-active substances: azadirachtin, salanin and nimbin in the neem oil and neem cake; the azadirachtin contents in the neem cake were 6 times higher than that in the neem oil. The neem oil consisted of 9 saturated and unsaturated fatty acids; among them, the oleic acid (C18=)contents were the highest (43%-48%) and the lauric acid (C12) contents were the lowest (trace-0.12%). The 15 pestiside formulations from the neem oil and neem oil with Bt were made and tested on Heliothis armigera and Plutella xylostella. The results showed that the neem oil itself and neem oil with Bt all affected to kill actively the insects.